2021
DOI: 10.1093/ofid/ofab302
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of the Endothelial Molecules ICAM-1, VEGF-A, and VEGFR2 in Microscopic Asymptomatic Malaria

Abstract: Background In malaria, clinical disease has been associated with increased levels of endothelial activation due to the sequestration of infected erythrocytes. However, levels and impact of endothelial activation and pro-angiogenic molecules such as vascular endothelial growth factor (VEGF)-A and its receptor VEGFR2 in asymptomatic malaria have not been well characterized. Methods Blood samples were obtained from community chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
2
2
0
Order By: Relevance
“…In this study, there was no association between parasite density and levels of ICAM-1 and VCAM-1. This is similar with the results of prior studies [15,16,19,20] which reported signi cant variances between uninfected controls and children with microscopic parasitaemia, but no signi cant correlation between parasite levels and these molecules.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, there was no association between parasite density and levels of ICAM-1 and VCAM-1. This is similar with the results of prior studies [15,16,19,20] which reported signi cant variances between uninfected controls and children with microscopic parasitaemia, but no signi cant correlation between parasite levels and these molecules.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the plasma concentrations of endothelial adhesion molecules; ICAM-1 and VCAM-1 were increased in cases with microscopic parasitaemia compared to uninfected controls. This nding aligns with previous studies [15,16,17], that reported an increase in ICAM-1 expression during malaria infections, and suggested its heightened binding with parasites displaying the appropriate Pf EMP-1 phenotype, indicating its potential signi cance in the development of cerebral malaria. It suggests that endothelial cells may react swiftly to the presence of the parasite in infected individuals, particularly when parasitaemia is visible by microscopy [15].…”
Section: Discussionsupporting
confidence: 92%
“…VEGF-A concentrations have been reported to be elevated in malaria and inflammatory diseases as a result of endothelial dysfunction 13 , 14 . In a recent study, there was no significant difference in VEGF-A concentrations between children with malaria and healthy ones 12 . Low concentrations have been associated with severe organ damage and mortality in sepsis, but it has not been a good indicator of prognosis 56 .…”
Section: Discussionmentioning
confidence: 85%
“…Endothelin-1 (ET-1) and asymmetric dimethylarginine (ADMA) are heparanase activators responsible for the breakdown of heparan sulfate (HS), which constitutes 50% to 90% of the glycosaminoglycan (GAG) family expressed on the surface of endothelial cells 7 . On the other hand, vascular endothelial growth factor-A (VEGF-A) controls vascular permeability, proliferation, survival, and inflammation of endothelial cells 11 , 12 . Vascular endothelial growth factor-A concentrations have been shown to be elevated in inflammatory diseases that may be the result of endothelial dysfunction in human 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%